Three Locally Clays as A Surfaces for Adsorption of Cephalexin Monohydrate From Aqueous Solution: Thermodynamic and Desorption Equilibrium - Al-Taweel, Saja S.; Isa, Sadoon A.; Al-Ani, Ramzi R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The adsorption of cephalexin.H2O from aqueous solution on attapulgite, bentonite and kaolin has been studied at the human body temperature (37.5ËšC) and at 5, 27, 47ËšC in 0.1M hydrochloric acid (pH 1.2). The value of pH 1.2 has been chosen to simulate the pH of stomach fluid. The clays show the following order: Bentonite > attapulgite > kaolin, for their activity to adsorb cephalexin.H2O. The charged clay particles can attract molecules either by electrostatic forces, for the molecules of oppositely charged, or by inducing dipole formation in the neutral molecule. The L-shaped adsorption isotherm indicated that drug molecules arrangement in a flat geometry on the clay surface. The results indicated the applicability of Langmuir isotherm for adsorption of drug on three clays. The amount of cephalexin.H2O adsorbed on the three clays was increased with increasing pH value from 1.2 to 5. At the acidic pH, the competition between cephalexin.H2O molecules and hydronium ions results in a reduction in adsorption process. At fixed temperature and pH, the adsorption of cephalexin.H2O on the three clays was increased with increasing the ionic strength of solution. The data showed a little increase in the amount of drug adsorbed by attapulgite and bentonite with increasing temperature, so the adsorption process appeared endothermic. The reverse was observed with adsorption of cephalexin.H2O on kaolin surface (exothermic).The extent of desorption of cephalexin.H2O from the clays increased when the concentration of drug increased. This result may refer to the difficulty of desorption of the drug at low concentrations, which reflects a relatively higher adsorbate - adsorbent interaction.